2016
DOI: 10.1007/s00268-016-3622-y
|View full text |Cite
|
Sign up to set email alerts
|

Injury Characteristics and Outcomes in Elderly Trauma Patients in Sub‐Saharan Africa

Abstract: Elderly trauma in a resource-poor area in sub-Saharan Africa is associated with a significant increase in hospital admissions and mortality. Significant improvements in trauma systems, pre-hospital care, and hospital capacity for older, critically ill patients are imperative.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 46 publications
6
12
1
Order By: Relevance
“…Compared to HICs, where more than 15% of trauma patients are elderly, the cohort of elderly patients admitted to the trauma unit during the study period made up a relatively small portion of the total number of trauma admissions [8, 20, 30–32]. In line with our findings, the few studies conducted in LMICs attributed less than 10% of trauma admissions to the elderly population [33–35].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Compared to HICs, where more than 15% of trauma patients are elderly, the cohort of elderly patients admitted to the trauma unit during the study period made up a relatively small portion of the total number of trauma admissions [8, 20, 30–32]. In line with our findings, the few studies conducted in LMICs attributed less than 10% of trauma admissions to the elderly population [33–35].…”
Section: Discussionsupporting
confidence: 84%
“…That said, intentionally inflicted injuries (due to community assault) and certain preventable MOIs (e.g., fall from height and PVCs) were common in our study, compared to findings from HICs [8, 23, 24, 37]. Studies conducted in LMICs showed similar assault rates to the current study [2, 32, 33, 35]. High assault rates may reflect the high crime rates, limited resources, and the relatively few programs in the public sector aimed at elderly trauma prevention evident in LMICs, such as SA, in contrast to most HICs [1, 45, 46].…”
Section: Discussionsupporting
confidence: 73%
“…Also, we should limit our prescription to the most needed medicines, and choose from the once daily intake or the most simple drug regimens [10]. In this case, adding twice daily vitamin B (that can be forgone) erroneously induced this elderly woman to quadruple her anti-hypertensive medicine with the risk of hypotension and falls [5, 6, 11]. Patients on ACEIs, especially the elderly, should monitored regularly for late onset adverse drug reactions [7].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple drug use combined with their fragile health predisposes them to adverse drug reactions, drug-drug interactions, and direct drug toxicity from potential overdosing [3]. They may even sustain physical injuries with eventual poor outcomes as a result of medicine use [46]. We report and discuss the lessons learnt from the case of an elderly woman in an urban setting in sub-Saharan Africa, who presented with problems of drug dosing, adverse drug effect, and drug-drug interaction that might prove useful in the future management of hypertension with angiotensin converting enzyme inhibitors (ACEIs).…”
Section: Introductionmentioning
confidence: 99%
“…3 Geriatric trauma in South Africa is almost certainly overshadowed by trauma in the young, and consequently under-reported in the literature. 11 Interpersonal violence (IPV) against the elderly is common and frequently under-reported. Paradoxically, there is very limited literature in South Africa that specifically focuses on this area.…”
Section: Introductionmentioning
confidence: 99%